Dalmatian Town - Croatian Hinterland: The Social Connections of the Ruling Elite of Zadar - Nikolić Jakus, Zrinka (2011)
The districts of Dalmatian cities had common borders with the medieval kingdom of Croatia, whose sovereign was the king of Hungary, but whose influence was rather weak before the mid-fourteenth century, when King Louis the Great of the Anjou dynasty managed to take the cities from the Venetian lordship, having crushed the power of the Croatian magnates who had opposed the effective royal power in the hinterland. Before that, especially during the thirteenth and the first half of the fourteenth century, the power of local magnates, especially of the Šubići kindred, had been much stronger. Contemporary sources indicate strong relations of various kinds between Dalmatian and Croatian nobility, despite the hostile attitude of local authors such as Thomas the Archdeacon of Split, who perceived them as the enemies of communal liberty. Of particular interest are the connections between the ruling elites of Zadar, which was the largest Dalmatian town, and its hinterland neighbours, since during this period, it was precisely Zadar of all Dalmatian towns that was under the most persistent Venetian rule. Among all the external factors that influenced the social and economic standing of the noble families of Zadar, that with the lords of the hinterland was the most important one. The Zaratin noble families whose origin has been established or at least suspected to be Croatian (meaning that their family name was of Slavonic origin) belonged to the richest and strongest in the city. One of the ways to come to a prominent status in the city was the intermarriage with the old elite. But then again, the Zaratin elite was also interested in intermarrying with the Croatian elite. However, the process of weakening the ties between the old kindred and their members who had established themselves in the city was quite rapid.
Projekt MZOS
ENG